MIGRASI RISEN DI PROVINSI NUSA TENGGARA BARAT BERDASARKAN HASIL SP 2010 DAN SUPAS 2015 - KABUL, LALU MUH. (GANEC SWARA, 2021)
The study is difference with previous studies where the study focused on recent migration among regency/municipality in one province namely West Nusa Tenggara. The aim of the study is to analysis pattern of in recent migration, out recent migration, and net recent migration. The study method used is descriptive quantitative. The result of study showed that in recent migration, out recent migration, and net recent migration increased between 2010 and 2015. The pattern of in recent migration and out recent migration between 2010 and 2015 was same increased in 7 regencies/municipalities and decreased in 3 regencies/municipalities. The pattern of net recent migration between 2010 and 2015 was difference negative net recent migration in 6 regencies/municipalities, zero net recent migration in 1 regency, and positive net recent migration in 3 regencies. Meanwhile, in 2015 it was negative net recent migration in 5 regencies/municipalities, and positive net recent migration in 5 regencies/municipalities. The change of negative net recent migration in 2010 toward positive net recent migration in 2015 it was occurred only in 2 regencies.